Determination of penicillin susceptibility of Streptococcus pneumoniae using the polymerase chain reaction. Issue 1 (February 1997) - Jalal, H; Organji, S; Reynolds, J; Bennett, D; O'Mason, E; Millar, M R
Abstract : AIM: To develop a polymerase chain reaction (PCR) based method to detect penicillin susceptibility in isolates of Streptococcus pneumoniae (SP). METHOD: PCR primers were designed to amplify differential nucleotide sequences of the penicillin-binding protein (PBP) genes 2b, 2x, and 1a in penicillin susceptible and resistant strains of SP. Primers derived from the PBP 2x and 2b genes were designed to amplify products from penicillin susceptible S pneumoniae (PSSP), whereas primers derived from the PBP 1a gene were designed to amplify gene sequences of penicillin resistant S pneumoniae (PRSP). RESULTS: Two hundred and thirty clinical isolates of SP from the USA, UK, Kenya, Romania, and the Kingdom of Saudi Arabia were tested. Of the isolates, 116 were penicillin susceptible, 65 were intermediately resistant, and 49 were highly resistant. PCR identified 108 (93%) of 116 of PSSP isolates, 55 (85%) of 65 intermediately resistant isolates, and all of the 49 highly resistant isolates of SP. The susceptibility of 16 (7%) isolates could not be determined using PCR. All of these 16 isolates had a minimum inhibitory concentration (MIC) of penicillin < 1 mg/l. None of the highly resistant isolates was identified as penicillin susceptible by PCR, although two of the isolates with intermediate resistance (MIC = 0.125 mg/l) were. CONCLUSION: Using primers that differentially identify the genotypes of susceptible and resistant strains of SP, PCR provides a rapid method for determining the penicillin susceptibility of SP isolates and could potentially be used for testing clinical samples.